Design of a Water Quality Monitoring Network on the Zimkan River in Kermanshah - Iraj Jabbari (جغرافیا و پایداری محیط)
Management, control and reduction of pollution, at first step, need to close monitoring of water quality that it is usually done by a wide network of stations. However, for various reasons, it is not feasible to establish such network in more basins of Iran. So, we need a network including a few readily available stations which is enable to reveal pollution amount of a river where is affected human activities on drainage basin system. In this research has been tried to design a water qualitymonitoringnetwork on the main rivers of Zimkan in the NorthWest of Kermanshah province.Therefore, pollution sources in the basin were identified at first and then amount of their emissions were presented by indices. The indices were combined together according to topographical and hydrological effect on contamination movement to main stream and then the vulnerable reaches was introduced. Amount of vulnerability of the river reaches was confirmed by matching of pollutants priorities and the results obtained from the water quality factors and heavy metals of water samples. According to vulnerability of reaches, nine monitoring locations were suggested at three situations: the confluence of tributaries which are subjected to intense human interference; The effect of two main branches of Zimkan in where they are close together at the end of catchment; and before and after the entrance of the main pollutant that it is possible to measure amount of their pollution. The advantage of this location finding is that it can make most flexibility monitoring measurements at different levels.